Faktor-Faktor Keterlambatan Pelaksanaan Proyek Gedung Hotel Alila Jakarta - Delimar, Lativa; Pamekas, R. (Jurnal Teknik Sipil, 2020)
Abstract Delays in the construction of Alila Hotel in Jakarta has become a very valuable and significant lesson for the construction industry. Amongst many other things, the factors behind the delay of the construction of projects are not always alike. This research aims to identify the different factors that cause delays in the construction of the Alila Hotel project. 68 factors that cause delays identified from the 6 activities have been used as a reference for primary data collection using questionnaires. Besides primary data, this research also uses secondary data obtained from project reports. Factor Analysis is used as a method for identifying the factors causing delays in the construction of the Alila hotel. The results of this research concluded that there are 3 significant factors that cause lateness in the Alila Hotel, which are financial (36.42%), management & administration (34.95%) and changes in design (28.63%). Abstrak Keterlambatan pelaksanaan proyek gedung hotel Alila Jakarta, telah menjadi salah satu pembelajaran yang baik bagi industri konstruksi. Sementara itu, faktor penyebab keterlambatan pelaksanaan proyek tidak selalu sama. Penelitian ini ditujukan untuk menetapkan faktor faktor penyebab keterlambatan pelaksanaan proyek bangunan hotel Alila Jakarta. Sebanyak 68 faktor penyebab keterlambatan dari 6 kegiatan utama digunakan sebagai acuan untuk pengumpulan data primer melalui kuesioner. Selain data primer, digunakan pula data sekunder yang berasal dari laporan pelaksanaan proyek. Analisis faktor digunakan sebagai metode untuk menetapkan faktor penyebab keterlambatan pelaksanaan proyek gedung hotel Alila tersebut. Hasil penelitian ini menyimpulkan bahwa terdapat 3 (tiga) faktor dominan penyebab keterlambatan proyek gedung hotel Alila yaitu faktor finansial (36.42%), manajemen & administrasi (34.95%) dan perubahan desain (28.63%).